Culturally Competent Care Training Reduces Health Disparities: A Mixed-Methods Systematic Review of Global Evidence - Fatma Lutfiyatus Sayyida; Indi Dwi Shofi Yanti; Anggun Novia Indah Fitri (Tarqabin Nusantara Group, 2025)
Culturally competent healthcare delivery has become essential in addressing the needs of increasingly diverse patient populations globally. This mixed-methods systematic review evaluates the effectiveness of cultural competence training for healthcare providers in reducing health disparities and improving clinical outcomes. Using PRISMA guidelines, a comprehensive search was conducted across major scientific databases, incorporating both qualitative and quantitative evidence published between 2010 and 2025. The synthesis reveals that structured training programs significantly enhance doctor-patient communication, increase patient satisfaction particularly among minority groups and contribute to more equitable diagnostic and treatment practices. Key mechanisms of impact include improved empathy, recognition of implicit bias, and the use of professional interpreters. Effective implementation strategies combine interactive workshops, e-learning modules, and experiential learning during clinical rotations. However, challenges such as inconsistent program design, lack of standardized frameworks, and limited institutional support hinder long-term sustainability. Strategic recommendations emphasize integrating cultural competence into medical education curricula, continuing professional development, accreditation standards, and licensure requirements. Institutional leadership, policy alignment, and interdisciplinary collaboration are critical for embedding cultural competence into routine healthcare practice. Findings underscore the necessity of longitudinal, competency-based training initiatives supported by national standards and performance monitoring systems. By fostering trust, promoting equity, and enhancing care quality, cultural competence training plays a pivotal role in transforming healthcare into an inclusive, patient-centered system capable of serving diverse global populations effectively.